The effects of different therapeutic modalities on cardiovascular risk factors in women with polycystıc ovary syndrome: A randomızed controlled study - Serkan Bodur; Ozgur Dundar; Mine Kanat-Pektas; Mehmet Ferdi Kinci; Levent Tutuncu (Elsevier, 2018)
Objective: This study was designed to evaluate the effects of 3 mg drospirenone/30 μg ethinyl estradiol (OC) alone or combined with 1700 mg metformin on metabolic risk factors. Materials and methods: In this randomized, prospective, controlled study, 87 non-obese (18-30 BMI) women of reproductive age (18-39) with polycystic ovary syndrome (PCOS) were assigned to control (n = 17), OC (n = 21), combination (n = 20) and metformin (n = 29) therapy groups. Results: Adiponectin levels changed −28.27%, −20.37% and 35.78% after OC, combination and metformin therapies, respectively. High sensitive C-reactive protein levels (hsCRP) changed with OC, combination and metformin therapies by 102.32%, 3.2% and −7.14%, respectively. Plasminogen activator inhibitor-1 levels decreased 41.34% in the metformin group. Apolipoprotein-B levels changed in a manner similar to changes in hsCRP levels. The homeostatic model insulin resistance index changed significantly between the groups following treatment (p = 0.001). Conclusion: Six cycles of treatments with OC alone may cause metabolic variables to deteriorate in non-obese women with PCOS. The addition of metformin to OC may ameliorate some aspects of this effect.